The First International Conference on ‘Processes and Palaeo-Environmental Changes in the Arctic: From Past to Present’ (PalaeoArc) - Lyså, Astrid; Örn Benediktsson, ĺvar; Emery, Andy; Gregoire, Lauren; Jennings, Anne; Morigi, Caterina; Müller, Juliane; O’Regan, Matt; Sarala, Pertti; Stokes, Chris; Szczuciński, Witold; Winsborrow, Monica (Geologos, 2019)
The First International Conference on ‘Processes and Palaeo-Environmental Changes in the Arctic: From Past to Present’ (PalaeoArc)